Determination of available transfer capability with implication of cascading collapse uncertainty. Issue 4 (1st April 2014) - Salim, Nur Ashida; Othman, Muhammad Murtadha; Serwan, Mohd Salleh; Fotuhi‐Firuzabad, Mahmud; Safdarian, Amir; Musirin, Ismail
Abstract : Available transfer capability (ATC) provides important information for power marketers and planning sectors in restructured power systems. The stochastic nature of power system behaviour, however, made ATC determination a difficult and complicated task. A stochastic framework has been established for ATC calculation with implication of uncertainties in transmission failures, hourly peak loads and system cascading collapse. The proposed ATC calculation framework is based on parametric bootstrap technique which enables generating random samples of system operating condition with uncertainty at a predefined confidence interval. The IEEE RTS‐96 network is employed to demonstrate the effectiveness of the proposed framework. The results presented indicate the significant impact of uncertainties on ATC value.